2017
DOI: 10.1155/2017/3280215
|View full text |Cite
|
Sign up to set email alerts
|

The Successful Treatment of a Case of Linear Psoriasis with Ixekizumab

Abstract: Linear psoriasis is an unusual clinical variation of psoriasis that manifests segmentally along the lines of Blaschko. A major differential diagnosis is inflammatory linear verrucous epidermal nevus (ILVEN). The treatment of linear psoriasis is often challenging, with inadequate response to biological agents reported in the literature. We report a case of a 25-year-old AfricanAmerican female who presented with asymptomatic hyperkeratotic papules along the lines of Blaschko and was subsequently diagnosed with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…There are at least two case reports of patients presenting with overlapping features of ILVEN and linear psoriasis that responded to treatments with a TNF‐ inhibitor, etanercept, 20 and IL‐17a inhibitor, ixekizumab 13 . Tanita et al reported a case of wide‐spread unilateral ILVEN that clinically and histologically mimicked psoriasis vulgaris but was distinguishable by immunohistochemical staining focused on the IL‐36γ/IL‐17a axis 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are at least two case reports of patients presenting with overlapping features of ILVEN and linear psoriasis that responded to treatments with a TNF‐ inhibitor, etanercept, 20 and IL‐17a inhibitor, ixekizumab 13 . Tanita et al reported a case of wide‐spread unilateral ILVEN that clinically and histologically mimicked psoriasis vulgaris but was distinguishable by immunohistochemical staining focused on the IL‐36γ/IL‐17a axis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Reported treatments for ILVEN include topical steroids, 4 topical tretinoin and 5-fluorouracil, 5 topical calcipotriene, 6,7 pulsed dye laser, 8 CO2 laser, 9 excimer laser, 4 surgical excision, 10,11 TNF-inhibitors 12 and IL-17a inhibitors. 13 Many of these treatments are derived from the psoriasis literature as some believe that the two entities share a common pathogenesis. 14,15 Clinically, both linear psoriasis and ILVEN can present as psoriasiform linear plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ustekinumab (interleukin 12/23) was also used in a linear psoriasis case reported by Weng and Tsai [ 18 ] after the patient failed to respond to methotrexate, acitretin, topical vitamin D 3 analogs, and steroids. Recently, Ghoneim et al [ 19 ] reported a case of a patient with linear psoriasis started on ixekizumab (interleukin 17), after failing to respond to topical steroids. After 4 months and 8 doses, the patient showed marked improvement, with the skin lesions almost resolved [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ghoneim et al [ 19 ] reported a case of a patient with linear psoriasis started on ixekizumab (interleukin 17), after failing to respond to topical steroids. After 4 months and 8 doses, the patient showed marked improvement, with the skin lesions almost resolved [ 19 ].…”
Section: Discussionmentioning
confidence: 99%